Childhood mortality and Child nutritional status of Bangladesh: A review on Demographic and Health Survey (Journal of Current and Advance Medical Research, 2015)
Background: Childhood mortality and child nutritional status of the developing countries are very much concerning issues of the world. Objective: The objective of this study was to evaluate the situation of childhood mortality and child nutritional status of Bangladesh with the comparative analysis and progress of childhood mortality and child nutritional status from 1993 to 2014. Methodology: In this regard this paper reviews the Bangladesh Demographic and Health Surveys (BDHS) conducted in 1993-94, 1996-97, 1999-2000, 2004, 2007, 2011 and 2014, which were analyzed on infant, child, under-five mortality and child nutritional status in detail. Result: The evidences reflected in BDHSs show that infant, child and under-five mortality in Bangladesh have declined steadily at least over the past years. However, differentials in trends and patterns of childhood mortality and even child nutritional status by the demographic determinants have not been explained elaborately. According to the 1993-1994 and the 2014 surveys found infant mortality two times, child mortality sex times and under-five mortality rates three times declined in 2014 than those were in 1993-94. On the contrary, stunning, wasting and underweight are also declined in 2014 comparatively than the last two decades but it is noted that wasting situation is not gradually declined. Conclusion: Bangladesh successfully declined the total number of childhood mortalities and nutrition related mortalities and complexities. Many non-government and government funded organizations should run some effective programs to overcome the situation completely in Bangladesh.Journal of Current and Advance Medical Research, 2015;2(2):42-46